Entrepreneurial Passion and Profitability of Small-Scale Poultry Farms in Delta State, Nigeria - Clinton Emmanuella (Journal of Behavioral Economics, Finance, and Management Insights, 2025)
Entrepreneurial passion is a key driver of business success, particularly in small-scale enterprises facing resource constraints and market uncertainties. This study examines the impact of entrepreneurial passion, measured by Sense of Purpose and Vision (SPV) and Emotional Attachment (EA), on the profitability of small-scale poultry farms in Delta State, Nigeria. Using a quantitative approach, survey data from 298 poultry farmers were analyzed through descriptive statistics, Pearson correlation, multiple regression, and ANOVA. Results indicate strong entrepreneurial passion among farmers, with SPV (r = 0.713) and EA (r = 0.702) showing significant positive correlations with profitability. Regression analysis confirms these effects, with SPV (β = 0.436, p = 0.001) and EA (β = 0.300, p = 0.014) contributing significantly to financial success. The model explains 89.1% of profitability variation (R² = 0.891), and ANOVA results (F = 595.857, p = 0.000) confirm its significance. The study concludes that fostering entrepreneurial passion enhances profitability and recommends targeted programs to strengthen farmers' vision, motivation, and emotional investment. Additionally, financial institutions should support passionate farmers to promote sustainable growth.